Pedagogical content knowledge desde el modelo de consenso refinado: revisión sistemática de la literatura (Memorias Sifored - Encuentros Educación UAN, 2022)
This work presents a systematic review on the methodological procedures approached in the investigation of Pedagogical content knowledge (PCK) from the refined consensus model (RCM) to know the tendencies of the researchers who have adopted the RCM that arises from the second summit of the PCK held in 2016 where the need is recognized to create a unified and simplified PCK taxonomy of its components through academic discussion to guide new research. For this review, it established Google Scholar, Scopus, ERIC as databases, where twelve research articles and two doctoral dissertations were collected in the period 2019 and 2021 that used the model as a theoretical framework in the design of their research. From this sample, methodological aspects such as the studied population, areas of knowledge, levels, components and types of PCK were analyzed; research approach and instruments used for the approximation of pedagogical content knowledge. The analysis of these aspects allowed us to glimpse a scarce sample collected in articles that use the refined consensus model of the PCK leading to consider that there is a lack of knowledge due to its recent appearance for the research field in education and absence in the approach of the PCK in biology teachers and mathematics, these considerations can guide new research under this frame of reference.
Keywords: database; methodologies; methodological analysis; systematic review; research approaches